Impacts of the environment on the vocal behaviour of Trichechus manatus manatus - SOUZA, Rebecca Nimrah Umeed de (2023)
This thesis aims to investigate the complexity of Antillean manatee, Trichechus manatus manatus, vocal communication in North-eastern Brazil. Additionally, this these aimed to detail how abiotic factors influence the vocal complexity and vocalisation propagation of this sub- species. The first part of this thesis is comprised of a bibliometric literature review, with the aim of exploring the available published literature on the effects of abiotic factors on the behavioural ecology and vocal communication of marine mammals. The second part focused on elucidating the complexity of the vocal repertoire of Antillean manatees and conspecific communication. Finally, the third part of this thesis focused on demonstrating the effects of abiotic factors on the vocal production and propagation of Antillean manatees. It was possible to register four call types in this thesis: Squeaks, Chirps, Trills and Pulse calls. The pulse call type was described for the first time here. The physical structure of the Squeak vocalisations presented differences at the individual level, suggesting the production of signature vocalisations by this sub-species. Communication between mother and calf manatees deserves particular attention, since we found that free-living mother-calf pairs and trios communicate using vocalisations with unique physical structures. Call rates of Antillean manatees were idiosyncratic according to time of day and tide level. However, call structure did not differ enough to differentiate the calls based on these factors. The behaviour of manatee call structures varied in terms of propagation, based on sex and animal origin (captive or reintroduction centre). Abiotic factors such as pH, salinity and temperature influenced call propagation. For example, there was a positive correlation between pH and relative amplitude for captive female calls during call propagation. There was also a positive correlation between temperature and bandwidth for captive male and calf calls. A negative correlation was found between pH and duration for older male calls. Overall, the results of this thesis reinforce that Antillean manatee vocalisations play an important role in vocal communication and likely contain information on individual identity, facilitating conspecific recognition. This thesis also showed that manatees alter their call pattern based on the time of day and/or tide level, but conserve vocalisation structure under these conditions. Manatee vocalisations suffer from little degradation over distance in natural pools in reef areas under different pH, temperature and salinity conditions. This may reflect an adaptation of these to animals to estuarine areas which experience constant abiotic alterations. Thus, the predicted changes in pH, temperature and salinity, caused by climate change will likely have little effect on Antillean manatee call propagation and consequently, their vocal communication. However, it is possible that the predicted increase in storm and flood frequencies may impact this sub-species more strongly.